Analisis Preventive Mantenance Pada Komponen Mesin Finger Joint Untuk Mengurangi Downtime Pada PT. Romi Violeta Sidoarjo - Nur Moh. Danang Andrian; I Nyoman Lokajaya (Jurnal Kendali Teknik dan Sains, 2023)
PT. Romi Violeta is a furniture company engaged in the production of rattan and wood products for the global market. The problem that often occurs is that the Finger Joint machine often experiences damage to the engine components. Therefore, the objectives of this research are to identify critical components in the Finger Joint machine, develop a maintenance scheduling for the machine's components, and compare the maintenance costs before and after implementing the scheduling. The analysis revealed that the Hydraulic component has a cumulative value of 40%, followed by the Cutter component with a cumulative value of 34.4%, and the Air Hose component with a cumulative value of 5.6%. Consequently, a preventive maintenance schedule was determined, with the Hydraulic component requiring maintenance every 31 days, the Cutter component every 36 days, and the Air Hose component every 207 days. This resulted in a reduction in maintenance costs from the previous amount of Rp.5,200,000 to Rp.1,210,847.